(I)∵xn+1-xn=(-)n,
∴xn=x1+(x2-x1)+(x3-x2)++(xn-xn-1)
=1+(-)+(-)2++(-)n-1
==+(-)n-1(4分)
当n=1时上式也成立,∴xn=+(-)n+1(n∈N*).(5分)
(Ⅱ)an=xn-=(-)n-1=(-)n+1.
∵T2n=a1+2a2+3a3++(2n-1)a2n-1+2na2n=(-)2+2(-)3+3(-)4++(2n-1)(-)2n+2n(-)2n+1①
∴-T2n=()3+2(-)4+3(-)3++(2n-1)(-)2n+1+2n(-)2n+2②
①-②,得T2n=(-)2+(-)3++(-)2n+1-2n(-)2n+2(8分)
∴T2n=-2n(-)2n+2=-(-)2n-(-)2n.T2n=-(-)2n-(-)2n=(1-).(10分)
(Ⅲ)由(Ⅱ)可得9T2n=1-.
当n=1时,22n=4,(2n+1)2=9,∴9T2n<Qn;(11分)
当n=2时,22n=16,(2n+1)2=25,∴9T2n<Qn;(12分)
当n≥3时,22n=[(1+1)n]2=(Cn0+Cn1+Cn2++Cnn)2>(2n+1)2.∴9T2n>Qn.
综上所述,当n=1,2时,9T2n<Qn;当n≥3时,9T2n>Qn.(14分)